ANALISIS KEMAMPUAN PENULISAN KALIMAT TUNGGAL SISWA KELAS IV SD XAVERIUS 4 PALEMBANG - Maria Grecia Novita (Jurnal PGSD Musi, 2020)
Education has an important role to format the character, and mentality of students and to develop science. One of the most important tools in education is language. Each language has its own system and rules including Indonesian Language. Less mastery of making sentence affects students in the learning process generally and communication in daily life. Certainly, elementary students are equipped with the ability to make sentences, especially with basic sentence patterns such as single sentences. Therefore, it is important to analyze the ability of fourth grade students to make a single sentence. This is to find out whether students are able to receive the lessons for making single sentences in accordance with the 2013 curriculum. From research in SD Xaverius 4 Palembang with qualitative research methods and triangulation analysis techniques the researcher found that IVB grade students were able to make single sentences. This is evidenced by students who get a score of 100 which is quite a lot reaching 85.18%, because the single sentence that is made has both of these core elements, and there are some students who get a score of less than 100 reaching 14.81%, due to single sentences that students do not have one of the core elements, there are even sentences that do not have these two core elements, so that the sentence cannot be said to be a single sentence.